HAZCI VE FAYDACI YAKLAŞIMIN MARKA BAĞI OLUŞUMUNDAKİ ROLÜ - TOSUN, NURHAN ZEYNEP (My University, 2018)
Ürün ve hizmetler arasındaki fonksiyonel farkların ortadan kalkmasıyla, markalar rekabette ayrışabilmek ve tüketici zihninde uzun süreli bir yer elde edebilme çabasına girmişlerdir. Bu noktada, tüketicilerle uzun süreli bir etkileşime önem veren işletmeler, tüketicilerde bir marka bağı oluşturma gayreti içerisindedirler. Yaşamları boyunca çeşitli markaları satın alan tüketiciler ise sınırlı markalarla aralarında uzun süreli bağlar geliştirmektedirler. İşletmeler, tüketicilerle aralarında güçlü ve sürekli bir marka bağı oluşturmak için reklam çalışmalarından faydalanmaktadır. Reklamlarda kullanılan hazcı ve faydacı mesajların marka bağı oluşturma etkisinden faydalanan işletmeler, oluşturdukları reklam içerikleriyle tüketicilerle markalar arasında uzun süreli bağ kurma çabasına girmektedirler. Bu çalışma kapsamında, reklamlarda kullanılan hazcı, faydacı ve her iki mesaj türünü içeren hem hazcı hem de faydacı mesajların tüketicilerde oluşan marka bağına yönelik rolü incelenmektedir. Araştırmada her bir reklam türünün belirlenen tanımlayıcı özellikler (yaş, cinsiyet, eğitim düzeyi, medeni durum, aktif olarak çalışma durumu, aylık gelir düzeyi ve daha önce IKEA mağazasını ziyaret etme durumu) açısından marka bağı oluşturmadaki rolü irdelenmiştir. IKEA reklamları üzerine gerçekleştirilen araştırma sonucunda, bağ oluşumunda en yoğun etkiyi reklamlardaki hem hazcı hem de faydacı mesajların birlikte kullanımının yaptığı görülürken, ikinci sırada hazcı mesajlar yer almakta ve bağın oluşumunda üç mesaj tipi arasında en düşük etkiye sahip mesaj tipinin faydacı reklam mesajlarının olduğu görülmüştür.

Functional differences between products and services have begun to disappear and this has seriously affected the market shares of brands and the competition conditions. In addition to this, today’s consumers are seen as individuals whose loyalty is weak and purchasing decisions are rapidly changing. It is thought that consumers will only be interested in the brands they feel close to, and they will use their purchasing preferences for these brands. At this point, it is assumed that consumers who buy and use many brands throughout their lifetime will develop strong ties with a limited number of brands. It is seen that consumers who develop an attachment to a brand tend to use that brand at all costs and they are faced with a negative feeling in the absence of brand. These individuals become fans of this brand and advocate the brand both on the internet and in real life. In such a case, consumers also show considerable resistance to the brand’s competitors. Individuals who have a sense of attachment to a brand spend their time and money, energy, etc., even if they have limited resources, to buy and use that brand. Moreover, consumers tend to ignore this when they have problems with the brands they are attached to. In summary, consumers who feel attached to any brand are thought to be loyal consumers who tend to buy that brand constantly. Therefore, brands have started to focus on the elements that will connect brands and consumers in order to be able to stand out from the competition, to get a long-term place in consumer mind, and to provide customer value. Brands build their all marketing components on establishing a strong attachment basis between consumers and brand. In this sense, the factors affecting brand attachment are mainly classified as compatibility with the individual, experience, ability to respond to consumer needs, brand reputation, trust, and quality. Advertising is another factor that helps businesses connect with consumers. Brands aim to establish attachment with consumers through advertising messages. At this point, the hedonist and utilitarian contents used in advertising helps brands connect with their consumers. Joy, fun, pleasure elements are generally used in hedonist advertisements. The advertisements focus on the pleasure elements consumers will obtain after using the product or service. In these advertisements, consumers are drawn into a fantasy world. The individuals who watch the advertisement experience excitement. In order to keep this experience alive, emotional appeal is utilized in advertisements. Thus, consumers feel good and have positive emotions. Another type of advertisement is the utilitarian advertisments. Informative ads usually show reasonable reasons for purchasing a promoted product. These advertisements highlight the product features and focus on the real, functional attributes that the consumer will acquire. In this type of advertising, the target audience is informed about the possession of the product, reasons for using the product and its requirements by a logical approach. This information contains factual, logical and objectively provable expressions. In summary, these advertisements emphasize the product’s attributes and its concrete benefits. In this context, the quality of the product, price value and performance are shown in utilitarian advertising contents. Utilitarian advertisings are aimed at convincing consumers that the characteristics and advantages of the advertised product or service are better than the competitors because of their informative nature. Utilitarian advertisings use rational advertising appeals for this purpose. In summary, businesses struggle to establish attachment between consumers and brands, through the use of hedonist and utilitarian advertising messages in advertisements. This study examines the role of hedonist, utilitarian and the advertisings including message types, hedonist and utilitarian, on the brand attachment established in consumers. In addition, the role of each message type in establishing brand attachment has also been examined in terms of identified descriptive attributes (age, gender, education level, marital status, active working status, monthly income level and previous visit to IKEA store). The research was conducted on IKEA ads. In the study, causal research method was used as a research type and convenience sampling method was used as a sampling type. In this context, an online survey was conducted on 502 men and women whose ages are between 18 and 35 constituted the target group of IKEA. At the end of the research, it is seen that the most intense effect to establish attachment has been created by the use of both hedonist and utilitarian messages in advertisements together. The second most intense effect has been created by hedonist messages and it is seen that the type of the message with the lowest effect among the t
THE ROLE OF HEDONIST AND UTILITARIAN APPOACH ON THE FORMATION OF BRAND ATTACHMENT